The Relationship Of Leukocyturia On The Incidence of Prominent Rupture of The Membrane in Preterm Pregnancy at the General Hospital of The University of Muhammadiyah Malang - Mochamad Ma'roef; Ayu Prima Kusuma Putri (Saintika Medika, 2019)
Prelabor rupture of the membrane (PROM) requires greater attention because of the high prevalence and its tendency to increase. The incidence of PROM at  37 weeks of gestation (aterm) is around 6.45-15.6% and about 2-3 percent of all single preterm pregnancies and 7.4% in twin preterm pregnancies. The purpose of this study was to determine the relationship between leukosituria and the incidence of premature rupture of membrane at < 37 weeks of gestation at the General Hospital of the University of Muhammadiyah Malang during 2015-2017. This is an analytic observational research with a cross-sectional study approach. Data were analyzed with Chi Square. Out of 36 samples that fit in the inclusion criteria, 18 patients had preterm PROM while 18 others had Aterm PROM. PROM mostly occurs in multigravida patients (58.3%, 21 patients). Patients with 38-39 weeks of gestation had the highest prevalence of PROM. Out of 18 Preterm PROM patients, 9 patients had leukocyturia. Only 1 aterm patients had positive leukocyturia. The result of this study showed a significant relationship between the incidence of PROM and preterm pregnancy.